Communication Networks for Smart Grids Making Smart Grid Real - Budka, Kenneth C.; Deshpande, Jayant G.; Thottan, Marina; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2014)
A 21st century clean energy economy demands a 21st century electricity grid, yet the communication networks of many utilities today are ill-equipped for smart grid evolution. This must-read text/reference presents an application-centric approach to the development of smart grid communication architecture and network transformation. The coverage includes in-depth reviews of such cutting-edge applications as advanced metering infrastructure, distribution automation, demand response, and synchrophasors as well as more traditional utility applications like SCADA systems. Providing detailed insights derived from the authors$1 (Bpivotal research on smart grid communications and extensive consulting experience, the book explains how electric power companies can transform their networks to best meet the challenges of tomorrow$1 (Bs smart grids. Topics and features: Examines a range of exciting utility applications made possible through smart grid evolution Describes the core-edge network architecture for smart grids, introducing the concept of wide area and field area networks (WANs and FANs) Explains how the network design paradigm for smart grids differs from that for more established data networks, and discusses network security in smart grids Provides an overview of communication network technologies for WANs and FANs, covering OPGW, PLC, and LTE and MPLS technology Investigates secure data-centric data management and data analytics for smart grids Discusses the transformation of a network from conventional modes of utility operation to an integrated network based on the smart grid architecture framework This comprehensive and practical guide will be of great interest to all professionals engaged in the planning, operation, and regulation of smart grids. Students studying courses on smart grids will also find the book to be an invaluable resource.s
Introduction to Smart Grids -- Elements of Power Systems for Networking Practitioners -- Elements of Communication Networking for Power Systems Practitioners -- Conventional Applications in Utility Operations -- Smart Grid Applications -- A Communication Network Architecture for the Smart Grid -- An Overview of Smart Grid Network Design Process -- Network Security -- WAN and FAN Technologies for the Smart Grid -- Smart Grid Data Management -- Communication Network Transformation -- Future of Smart Grid Communication Networks -- Icons Used in Figures -- Smart Grid Characterization -- Fourier Analysis -- Voice over IP and Quality of Service.
Keywords: Computer science; Computer communication systems; Data encryption (Computer science).; Power electronics; Computer Science; Computer Communication Networks; Data Encryption; Power Electronics, Electrical Machines and Networks; Electronic books